The image of Khon Kaen University under the undergraduate view - Chaisiwamongkol, Wichuda; Ungpansattawong, Supunnee; Maneesriwongul, Amnuay; Naimsanit, Rungson; Krongyuth, Pramote; Tongprasit, Yuparporn; Srisodaphol, Wuttichai; Pattanakul, Kulaya (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this research was to survey the image of Khon Kaen University image under the undergraduate view. Studied samples consisted of 380 undergraduate students from 18 faculties. They were classified into 3 strata based on their fields of study; health sciences, science and technology, and humanities and social sciences groups. The surveys covered seven attitudes; 1) vision and mission 2) leading university in the ASEAN 3) learning-based, research-based and quality-based university 4) good management 5) personnel or staff 6) community and nation development, and social responsibility and 7) communications and Public Relations with a total of 40 questionnaires and each with 10 scores. For all groups, average score about attitudes of images was 7.57 (B+) as a very good level. The highest average scores of the attitude was learning-based, research-based and quality-based university with 7.90 (B+) as a very good level. The lowest average scores of the attitude were Personnel or Staff with 6.83 as a good level (B). On the average score by group of the health sciences had lower average score than others in all items.